2018
DOI: 10.1159/000491665
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-34a Attenuates Metastasis and Chemoresistance of Bladder Cancer Cells by Targeting the TCF1/LEF1 Axis

Abstract: Background/Aims: Chemoresistance is largely responsible for relapses of bladder cancer during clinical therapy. However, the molecular mechanisms involved in the chemoresistance of bladder cancer are unclear. Growing evidence supports the theory that microRNAs (miRNAs) play an important role in chemotherapeutic drug resistance because they are downregulated in many malignancies that have been implicated in the regulation of diverse processes in cancer cells. More specifically, the extent and precise mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…MicroRNAs (miRNA), a class of small and non-coding RNA, directly regulate a variety of biological processes of mRNAs in multiple cancer types [13]. Increasing evidences demonstrated that miRNAs exert influences on inhibiting or promoting invasion, migration and apoptosis in bladder cancer [16, 17]. For instance, miR-520f could reverse EMT and inhibit metastasis by targeting ADAM9 and TGFBR2 [18].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNA), a class of small and non-coding RNA, directly regulate a variety of biological processes of mRNAs in multiple cancer types [13]. Increasing evidences demonstrated that miRNAs exert influences on inhibiting or promoting invasion, migration and apoptosis in bladder cancer [16, 17]. For instance, miR-520f could reverse EMT and inhibit metastasis by targeting ADAM9 and TGFBR2 [18].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been conducted to directly regulate the expression of LEF1 by miRNAs, mainly focusing on tumor diseases. miR-34a increased chemosensitivity in BIU87/ADR cells by targeted inhibition of the TCF1/LEF1 axis [48]. miR-22, a direct target of H19, binds to the 3′UTR of LEF1 to inhibit its expression and reverse the effect of H19 on nucleus pulposus cells, thereby inhibiting the Wnt/β-catenin pathway [49].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, miR-34a could be involved in the Wnt pathway by specifically repressing LEF1 to regulate the EMT process in prostate cancer [68]. miR-34a contributes to the chemosensitivity of BIU87/ADR, an epirubicin (EPI) chemoresistant cell line, by inhibiting the TCF1/LEF1 axis in bladder cancer [69].…”
Section: Mir-34a Regulates Emt In Cancer Cellsmentioning
confidence: 99%